Perspectives of human biology in Poland, with special emphasize to auxology - Wolański, Napoleon; Siniarska, Anna (Studia Ecologiae et Bioethicae, 2009)
Protoculture has already existed in animals and is manifested by using a natural object as a tool or by coping the habits of another animals being successful in doing something. At the beginning it was the practice of everyday life, the act of survival, what can be understood as “technique”. After that the process of rational cognition (theory) takes place, and innovative theories propagate the “science” development. Science discovers rules in our nature and society as well as in human activity called culture. Science is a certain sphere of consciousness including self-consciousness, thus science could be created together with consciousness, as a product of thinking mind. Such mind is possessed by humans only. Probably, science has been developed till nowadays following the technological progress. Most likely generalizations of tools behaviors and social contacts have caused brain development and favored abstraction, future vision and articular speech. Since the beginning of Civilization, science had been created not because there was a demand for it, but as the reflection on human life, the result of technical achievements, and as the answer for the question “why does it happen?” When man has protected his basic requirements and received nutritional surplus above daily needs, he has gained a little free time for contemplation, and his reflections have directed the civilization development. In this case, the only way: “thinking is the action” is not adequate. Science, as a turn, causes a revolution in technology, but does not serve for small engineering improvements, as revolutions have also a destructive face. As long as evolution strengthens and improves existing system, revolution destroys the old system, and the new one may fail to be good. If science has been interfered in technique continuously, the technical progress which makes our life easier would have been stopped. Science takes into account cognition of existence, as well as, the realities which are still unknown according to their being and functions. Propagation of knowledge belongs to education, whereas invention of artifacts (things which do not come into existence simultaneously) belongs to technique, engineering and art. The main aim of science is the summary (generalization) of technical and engineering achievements, which may serve as verification of the process of cognition. Science, as a tool of intellectual cognition, should provide a better contact with surrounding world, nature and universe. It should also serve human development and help to understand the sense of our existence, promote ability of thinking and intellectual self-realization. In the context of previous considerations, there are four, very important problems in human biology, especially in auxology. The first one concerns directions of studies on the basis of current information concerning mechanism of ontogeny causing variation in body build and functions of contemporary human populations. The second one deals with dissemination of knowledge in human biology, on the university and general levels. The third problem is about application of human biology and ecology in medical and pedagogic practice, as well as concerns the evaluation of planned engineering actions, changes in human life environment. There is also a fourth problem, which varies in particular countries, and it includes the state of each scientific anthropological atmosphere. In most of countries, physical anthropology is still understood as natural history on Man, his variation in time and space, and as the biological base for social practices. However, the main accent which included anthropogenesis, rasogenesis, and ethnogenesis has changed into mechanisms of adaptation to changing environment (also understood as living conditions and social surroundings) during ontogeny, and causes the mechanisms of evolution (phylogeny is recapitulated during the first phases of ontogeny).